2018
DOI: 10.1002/mds.27338
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term safety and efficacy of levodopa‐carbidopa intestinal gel in advanced Parkinson's disease

Abstract: A BST RACT : Background: Levodopa-carbidopa intestinal gel (designated as carbidopa-levodopa enteral suspension in the United States) provides stable plasma levodopa concentrations and reduces motor fluctuations in advanced Parkinson's disease patients through continuous delivery of levodopa via percutaneous endoscopic gastrojejunostomy. We report long-term safety and efficacy outcomes from an open-label phase 3 treatment program. Methods: PD patients (n 5 262) who completed a 12-week double-blind study and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
80
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 36 publications
12
80
2
2
Order By: Relevance
“…Data were collected from patients with advanced PD who participated in a 12-week, randomized, double-blind, active-controlled parallel-group study [9] (NCT00660387/NCT0357994) and either the subsequent 52-week open-label extension study [12] (NCT00360568) or a separate 54-week open-label study [10] (NCT00335153). Patients were then eligible to enroll in an ongoing open-label, continued-access multinational extension study [11] (NCT00660673) where they could continue treatment until the product was available locally. e enrollment period was from November 2009 through October 2012.…”
Section: Study Design and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were collected from patients with advanced PD who participated in a 12-week, randomized, double-blind, active-controlled parallel-group study [9] (NCT00660387/NCT0357994) and either the subsequent 52-week open-label extension study [12] (NCT00360568) or a separate 54-week open-label study [10] (NCT00335153). Patients were then eligible to enroll in an ongoing open-label, continued-access multinational extension study [11] (NCT00660673) where they could continue treatment until the product was available locally. e enrollment period was from November 2009 through October 2012.…”
Section: Study Design and Treatmentmentioning
confidence: 99%
“…Levodopa-carbidopa intestinal gel (LCIG, also known as carbidopa-levodopa enteral suspension in the United States) was developed to deliver continuous administration of levodopa treatment via percutaneous endoscopic gastrojejunostomy (PEG-J), resulting in improved motor function and fewer drug fluctuations in patients with advanced PD. Results from subsequent clinical studies using this approach have demonstrated improvements in clinical outcomes, including significant improvements in "Off " time and "On" time without troublesome dyskinesia (TSD), quality of life, and improvements in activities of daily living [8][9][10][11][12]. Although there is robust evidence for the clinical benefit of LCIG in patients with advanced PD, there are no studies assessing the safety and efficacy of high doses (≥2000 mg), and information on the use of high-dose LCIG is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, intestinal gel infusions of L-dopa support the concept of continuous DA receptor stimulation needed to prevent dyskinesias induced by L-dopa. 10,142 In addition to motor complications and nausea, many other adverse effects may be associated with Ldopa treatment. Hallucinations and confusion are the most adverse effects e in the elderly and in those with preexisting cognitive dysfunction.…”
Section: Issn: 2357-0547 (Print)mentioning
confidence: 99%
“…8 DA precursor (L-dopa) was found to be qualified in alleviating the symptoms of PD and till now, the main PD management is the chronic oral administration of L-dopa. 9,10 With the discovery of a toxin-induced PD in humans in the early1980, the second advance in PD research came. An illicitly manufactured opiate contaminated with 1-methyl-4phenyl-1,2,3,6-tetrahydropyridine (MPTP) whose users rapidly produced progressive, L-dopa-responsive parkinsonism like to what reported in sporadic PD.…”
Section: Introductionmentioning
confidence: 99%